Qalbu Dalam Perspektif al-Qur’an - Ramadhan Lubis; Anisa Pratiwi; Rili Ritami Sipahutar (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This article discusses the role of the qalbu (heart) in humans based on the perspective of the Koran. The heart is an element of the human soul which has an important role in determining good or bad actions. In the Qur'an, the heart is associated with a clean, pure and gentle heart, which are characteristics valued by Allah. This article also explains that the heart has a role in accepting and rejecting guidance from Allah SWT, and how the heart can play a role in studying and interpreting His creation to reach a higher level of faith. Apart from that, this article discusses the potentially good and bad characteristics of the heart, as well as how humans can improve the quality of the heart through actions that are in accordance with Islamic teachings. Through understanding the role of the heart, it is hoped that humans can draw closer to Allah SWT. and develop a spiritually good personality.